The Effect Of Atmosphere Coffee Shop And Customer Experience On Customer Satisfaction At The Bagi Kopi Branch In Kiara Artha Park, Bandung - Nazila Laila Karomah; Tanty Sondari; Ahmad Johan (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to determine the influence of atmosphere coffee shop and customer experience on customer satisfaction at the Bagi Kopi branch in Kiara Artha Park, Bandung. This study employs a quantitative method with a descriptive and confirmatory approach. The results of the study indicate that the atmosphere coffee shop has a positive but insignificant effect on customer satisfaction (t = 1.456, p > 0.001), whereas customer experience has a positive and significant effect on customer satisfaction (t = 8.134, p < 0.001). Conversely, the atmosphere coffee shop and customer experience significantly influence consumer satisfaction (F = 291.410). These results imply that when the atmosphere and customer experience meet consumer expectations, satisfaction with the products and services provided is achieved.